2017
DOI: 10.1016/j.neurobiolaging.2017.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen enhances hippocampal gray-matter volume in young and older postmenopausal women: a prospective dose-response study

Abstract: Estrogen administration following menopause has been shown to support hippocampally-mediated cognitive processes. A number of previous studies have examined the effect of estrogen on hippocampal structure to determine the mechanism underlying estrogen effects on hippocampal function. However, these studies have been largely observational and provided inconsistent results. We examined the effect of short-term estradiol administration on hippocampal gray matter volume in a prospective study with multiple doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…There are recent reports of decreased frontal gray matter in MHT users versus nonusers, and several studies have focused on the hippocampus, with one showing a positive short‐term (i.e., 3‐month) treatment effect of relatively high doses of estradiol compared with low doses and placebo, but two others reporting null effects when comparing current, past, and nonusers . The pattern of findings could reflect MHT formulation (e.g., studies reporting null effects grouped users of estrogen‐only and combined therapies), or neural plasticity occurring around the MHT transition.…”
Section: Menopausal Hormone Therapymentioning
confidence: 99%
“…There are recent reports of decreased frontal gray matter in MHT users versus nonusers, and several studies have focused on the hippocampus, with one showing a positive short‐term (i.e., 3‐month) treatment effect of relatively high doses of estradiol compared with low doses and placebo, but two others reporting null effects when comparing current, past, and nonusers . The pattern of findings could reflect MHT formulation (e.g., studies reporting null effects grouped users of estrogen‐only and combined therapies), or neural plasticity occurring around the MHT transition.…”
Section: Menopausal Hormone Therapymentioning
confidence: 99%
“…The following tests were used: spatial working memory (SWM), spatial span (SSP), pattern recognition memory (PRM), 5-choice reaction time (RTI), and match to sample visual search (MTS). The tests chosen activate areas of the brain that are associated with cognitive decline during the menopausal transition and that are sensitive to hormonal changes, including the hippocampus [54] and prefrontal cortex [5]. SWM and SSP activate the temporal and frontal lobe regions of the brain; PRM activates the temporal lobe, hippocampus and amygdala; RTI and MTS activate the fronto-striatal circuitry [55].…”
Section: Cognitive Functionmentioning
confidence: 99%
“…Our primary hypothesis was that in transgender women presenting with surgically induced hypogonadism, estradiol exerts neuroprotective effects that can be measured by means of gray matter tissue increase. Specifically, we expected an increase in CTh, similar to those observed in women following MHT [18][19][20][21], an effect opposite to cortical GMV loss demonstrated during androgen suppression in men [24].…”
Section: Introductionmentioning
confidence: 63%
“…Moreover, in menopause, studies have shown differential effects of estradiol on gray matter. For instance, despite some studies in menopause indicating reductions in gray matter after MHT [22,23], the thinning phenomenon is not yet completely understood, considering the cortical sparing effect promoted by MHT shown in GMV and CTh in other studies [18][19][20][21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation